Downregulation of miRNA‐141 in breast cancer cells is associated with cell migration and invasion: involvement of ANP32E targeting. (21st February 2017) - Li, Ping; Xu, Tao; Zhou, Xin; Liao, Liangying; Pang, Guolian; Luo, Wan; Han, Lu; Zhang, Jiankun; Luo, Xianyong; Xie, Xiaobing; Zhu, Kuichun
Abstract: MicroRNAs (miRNAs) regulate many cellular activities, including cancer development, progression, and metastasis. Some miRNAs are involved in breast cancer (BC) migration and invasion, thus affect patients' prognosis. Microarray analysis was performed to compare miRNA expression in BC tissues, and results confirmed by qPCR. BC cell migration and invasion were studied in vitro with MDA‐MB‐231 cells using microplate transwell assays. miRNA targeting was investigated using luciferase assays, qPCR, and Western blot analysis in cells with overexpression of miRNA mimics. Knockdown of miRNA targets was performed using target siRNA lentiviral infection. Results show that microRNA‐141 (miR‐141) was downregulated in breast cancer tumor tissues compared with matched surrounding tissues. Downregulation of miR‐141 expression correlated with tumor stage, lymph node involvement, and expressions of PCNA, Ki67, and HER2. Overexpression of miR‐141 inhibited BC cell proliferation, migration, and invasion in vitro. ANP32E gene was selected as one putative target for further studies based on results from in silico analysis. Results from a dual‐luciferase reporter system suggested ANP32E as a direct target of miR‐141. Overexpression of miR‐141 downregulated ANP32E expression at both mRNA and protein levels in BC cells. Knockdown of ANP32E inhibited BC cell proliferation, migration, and invasion in vitro, mimicking the effect of the overexpression of miR‐141. Our study revealed important roles miR‐141 plays in BC growth and metastasis. Moreover, for the first time, we identified ANP32E as one of the miR‐141 targets, and demonstrated its involvement in the regulation of cell proliferation, migration, and invasion. Abstract : miR‐141 is downregulated in breast cancer (BC) tissue. Overexpression of miR‐141 inhibits BC cell migration and invasion. miR‐141 inhibits BC cell migration and invasion by directly targeting ANP32E.